Hemostatic therapy in experimental intracerebral hemorrhage associated with Rivaroxaban - Zhou, Wei; Zorn, Markus; Nawroth, Peter Paul; Veltkamp, Roland (Stroke, 2013)
Background and Purpose— - - Rivaroxaban has recently been approved for stroke prevention in atrial fibrillation. However, lack of an effective antidote represents a major concern in the event of intracerebral hemorrhage (ICH). The aims of the present study were to establish a murine model of ICH associated with rivaroxaban, and to examine the effectiveness of different hemostatic factors in preventing excess hematoma expansion. - - Methods— - - In C57BL/6 mice receiving 10 or 30 mg/kg rivaroxaban by gastric gavage, plasma concentration, prothrombin time, and coagulation factor activities were measured repeatedly. Thirty minutes after inducing ICH by intrastriatal collagenase-injection, mice received an intravenous injection of either saline, prothrombin complex concentrate (100 U/kg), murine fresh frozen plasma (200 μL), or recombinant human Factor VIIa (1 mg/kg). ICH volume was quantified on brain cryosections and using hemoglobin spectrophotometry 24 hours later. - - Results— - - Rivaroxaban in 30 mg/kg dose substantially increased the hematoma volume in ICH induced by 0.060 U collagenase. Prothrombin complex concentrate, fresh frozen plasma, or Factor VIIa prevented excess hematoma expansion caused by anticoagulation. Prevention of hematoma expansion by prothrombin complex concentrate was dose-dependent. None of the 3 agents completely corrected the prolonged prothrombin time, although they restored the activities of deficient FII and X. - - Conclusions— - - Prothrombin complex concentrate, Factor VIIa, and fresh frozen plasma prevent excess intracerebral hematoma expansion in a murine ICH model associated with rivaroxaban. The efficacy and safety of this reversal strategy must be further evaluated in clinical studies.